True Grit : American Prints from 1900 to 1950 - Nemerov, Alexander; Glisson, James; Schrader, Stephanie (Book collections on Project MUSE., 2019)
"An examination of thirty-eight prints by American artists from the first half of the twentieth century"--Provided by publisher.